Sharing Class Program in Increasing Pakuwon Village Community Understanding About COVID-19 - Ai Eva Aryani; Dewi Handayani; Mira Ilhami; Siti Rahmi Rahmawati (Fakultas Kewirausahaan Universitas Garut, 2022)
Abstract COVID-19 is a disease caused by the Coronavirus that emerged in 2019. Currently, the death rate due to COVID-19 in Indonesia is very high, even higher than the world death rate. Public knowledge about COVID-19 and its dangers to oneself is still very low. The Sharing Class program aims to increase public understanding of COVID-19 and its dangers for themselves so that people will be more disciplined in following government regulations as an effort to prevent COVID-19. In addition, this program is also a forum to accommodate all public questions about COVID-19. The method used in this community service activity is socialization against COVID-19 by providing information about steps to deal with COVID-19 as well as adapting new habits during the pandemic. This program is carried out online through the WhatsApp group in three meetings for one month. As a result, the residents of Pakuwon Village are very enthusiastic in gaining knowledge about COVID-19. It is hoped that the public will have the knowledge to deal with COVID-19. Abstrak Masyarakat Indonesia mayoritas sudah mengenal swamedikasi. Nyeri merupakan salah satu gejala penyakit yang dapat diatasi melalui swamedikasi. pengetahuan masyarakat mengenai swamedikasi masih tergolong buruk dan perilaku swamedikasi di Indonesia masih berjalan tidak rasional. Tujuan dari penelitian ini mengetahui pengaruh dari pemberian edukasi terhadap pengetahuan dan sikap penggunaan obat analgesik untuk swamedikasi nyeri. Penelitian ini menggunakan desain praeksperimental, dengan rancangan one group pretest posttest. Instrumen yang digunakan berupa kuesioner yang telah diuji validitas dan reabilitasnya. Hasil penelitian menunjukkan terdapat perbedaan tingkat pengetahuan dan sikap setelah pemberian edukasi (p<0,05). Edukasi penggunaan analgesik untuk swamedikasi nyeri menunjukkan peningkatan tingkat pengetahuan dan sikap responden.